ATTITUDE OF ONLINE USERS TOWARDS CASHLESS TRANSACTION SYSTEM - Anandhi, G.; Jerome, v. Bastin (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this paper is to find the online users towards cashless transaction system in Tiruchirappalli City. The cashless transaction system is reaching its growth day by day, as soon as the market become globalized and with the digital growth of public sector, the people moves from cash to cashless system. However, in a developing economy like India, where 40% of the population is excluded from the formal financial system, where the penetration of alternative mediums of exchange is limited, cash plays a crucial role as a medium of exchange. The objective of this study is to understand consumers’ attitude of online users towards cashless transaction system in Tiruchirappalli City and also to understand consumers usage related to cashless transactions. The current study has used survey method for collecting primary data of 500 respondents using convenience sampling technique for the empirical analysis of consumers’ attitude towards doing cashless transactions.